GETTERING OF COPPER TO OXIDATION INDUCED STACKING-FAULTS IN SILICON - Decoteau, M; Wilshaw, P; Falster, R (1990)
Results are presented from an investigation concerning the influence of oxidation-induced stacking faults, their bounding partial dislocations, and mechanically-induced surface pits on the precipitation behaviour of copper in silicon. Controlled amounts of copper are diffused into wafers containing such defect structures so that their effect on precipitation behaviour can be studied using TEM and preferential etching techniques. These studies indicate the relative efficiencies of the different defect types as centres for the precipitation of copper and also reveal the different precipitate structures which are produced.